THE STATUS OF STATE CIVIL APPARATUS COMMISSION IN STATE SYSTEM OF INDONESIA - Desi Susanti; Edra Satmaidi; Ardilafiza Ardilafiza (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
Along with the formation of institutions in Indonesia, it is known by the term Non-Departmental Government Institutions (LNDP) which after the enactment of the Law on State Ministries which changed department term into ministry, but at the initiative of several ministries, there were also other terms that were introduced, namely Non-Structural Institutions (LSN). One of the NonStructural Institutions (LSN) currently is State Civil Apparatus Commission. In Article 1 number 19 of Law Number 5 of 2014 concerning State Civil Apparatus is stated that the Commission of ASN, which abbreviated as KASN, is a non-structural institution which independent and free from political intervention to create ASN employee that professional and performs to provide services fairly and neutral and become adhesive and unifier of the nation. KASN was formed to supervisethe implementation of basic norms of the ethic code and behavior code of ASN as well as the Application of the Merit System in ASN’s policy and management.